Hubungan Rheumatoid Arthritis dengan Kejadian Insomnia pada Usia Lanjut : Relationship between Rheumatoid Arthritis and Insomnia in Old Age - Sri Wulandari; Warda Anil Masyayih; Rista Dian Anggraini; Hany Puspita Aryani (Journal of Holistics and Health Sciences (JHHS), 2023)
One of the health problems often experienced by the elderly is rheumatoid arthritis. Joint disorders experienced by people with rheumatoid arthritis will have an impact on physical problems such as insomnia and will later affect sleep quality. Design correlational analytical research with a cross-sectional approach. The sample was all elderly people with rheumatoid arthritis as many as 30 respondents using the smapling purposive sampling technique. Data collection using KSPBJ insomnia rating scale questionnaires. Analyse data with Spearman’s Rho test with 0.05 significance. The results of the study were known that in respondents who experienced rheumatoid arthritis with severe pain all experienced severe insomnia, which was 13.3%. Meanwhile, in respondents who experienced rheumatoid arthritis with mild pain, all experienced mild insomnia, which was 36.7%. The results of the data analysis with the Spearman Rho test found that there was a relationship between rheumatoid arthritis and insomnia in old age in Kreteranggon Village, Sambeng District, Lamongan Regency (ρ =0,000, α=0.05, r=0.699). Based on the description above, it can be concluded that there is a relationship in the strong category between rheumathoid arthritis and the incidence of insomnia. ABSTRAK Salah satu masalah kesehatan yang sering dialami oleh lansia adalah rheumatoid arthritis. Gangguan sendi yang dialami penderita rheumatoid arthritis akan berdampak pada masalah fisik seperti insomnia dan nantinya akan berpengaruh pada kualitas tidur. Rancangan penelitian analitik korelasional dengan pendekatan cross sectional. Sampelnya semua lansia penderita penyakit rheumatoid arthritis sebanyak 30 responden dengan menggunakan teknik sampling purposive sampling. Pengumpulan data menggunakan kuesioner KSPBJ insomnia rating scale. Analisa data dengan uji Spearman’s Rho dengan signifikasi 0,05. Hasil Penelitian diketahui bahwa pada responden yang mengalami rheumatoid arthritis dengan nyeri berat seluruhnya mengalami insomnia berat yaitu sebanyak 13,3%. Sedangkan pada responden yang mengalami rheumatoid arthritis dengan nyeri ringan seluruhnya mengalami insomnia ringan yaitu sebanyak 36,7%. Hasil analisa data dengan uji Spearman Rho didapatkan ada hubungan rheumatoid arthritis dengan kejadian insomnia pada usia lanjut di Desa Kreteranggon Kecamatan Sambeng Kabupaten Lamongan ( ρ =0,000, α=0,05, r=0,699).  Berdasarkan uraian diatas dapat disimpulkan bahwa Ada hubungan dalam kategori kuat antara rheumathoid Arthritis dengan kejadian insomnia.